The Impact of Child Dental Caries and the Associated Factors on Child and Family Quality of Life - Marziyeh Shokravi; Fatemeh Khani-Varzgan; Mohammad Asghari-Jafarabadi; Leila Erfanparast; Behjat Shokrvash (International Journal of Dentistry, 2023)
Introduction. Dental caries are considered as common health hazards and a serious lifelong threat to general health and quality of life. The present study aimed at identifying the impact of child dental caries and the associated factors on both child and family quality of life (QoL). Material and Methods. In this cross-sectional study, preschool children were selected randomly through clustered sampling from five educational districts in Tabriz, Iran, 2016. To assess the QoL related to oral health, the Early Childhood Oral Health Impact Scale (ECOHIS) was used. Clinical oral examination was performed to assess the presence of caries through the index of decayed, missing, and filled teeth (dmft). Descriptive and analytic statistical methods were used. To assess the underlying predictors of ECOHIS as a whole scale and the dimensions as a linear regression model were used as univariate and multivariate. Results: Out of 756 children under 7 years old, 51.5% boys, mean (M) standard deviation (SD) of age 5.76 (0.78). About 85% of children had dental caries. The predictors of suboptimal ECOHIS related to both general and child dimensions were child age 6 year and above: r (756) = 2.43, and P≤0.001, low-socioeconomic status: r (756) = 3.36 and P<0.001 and high dmft: r (756) = 9.10 and P<0.001. The predictors of suboptimal ECOHIS related to family domain were sex (girl): r (756) = 0.39 and P=0.047; mother education (under12): r (756) = −0.92 and P<0.001; mother job (employed) as univariate: r (756) = 0.71 and P=0.002); and dmft: r (756) = −0.58 and P=0.035. Conclusion. Adverse oral health of children imposes adverse effects on the QoL of children and families. Children’s age, family socioeconomic level, presence of dental caries, child’s gender, and mother’s educational level were associated with the impact on QoL.